Social and structural housing conditions influence the development of a depressive-like phenotype in the learned helplessness paradigm in male mice - Chourbaji, Sabine; Zacher, Christiane; Sanchis-Segura, Carla; Spanagel, Rainer; Gass, Peter (Behavioural brain research, 2005)
Structural and social factors are known to play a crucial role in the pathogenesis of depression. Since animal models of depression are a major tool to gain insights into the mechanisms involved in the pathophysiology of this disease it is important not only to exploit but also to be aware of factors that may affect these models. As housing represents a fundamental external factor, which is controversially debated to affect the animals’ emotionality, this study aimed to investigate the impact of different social and structural housing conditions on the development of a depressive-like syndrome in the learned helplessness paradigm. Group housing in an impoverished environment led to an increased vulnerability in the learned helplessness paradigm. Groups that were housed enriched, however, were less helpless. Furthermore impoverished conditions did not increase the vulnerability in single housed animals. Regarding emotionality in the animals, basal anxiety was reduced and the exploration was enhanced by group housing and enriched environment. These results suggest that housing conditions significantly influence the outcome of learned helplessness studies.